High Seropositivity of Brucella melitensis Antibodies among Pregnant Women Attending Health Care Facilities in Mwanza, Tanzania: A Cross-Sectional Study - Helmut A. Nyawale; Michael Simchimba; Joseph Mlekwa; Fridolin Mujuni; Elieza Chibwe; Prosper Shayo; Elifuraha B. Mngumi; Khadija S. Majid; Mtebe Majigo; Stephen E. Mshana; Mariam M. Mirambo (Journal of Pregnancy)
Background. Brucellosis is one of the most prevalent zoonotic neglected tropical diseases across the globe. Brucella melitensis (B. melitensis), the most pathogenic species is responsible for several pregnancy adverse outcomes in both humans and animals. Here, we present the data on the magnitude of B. melitensis antibodies among pregnant women in Mwanza, Tanzania, the information that might be useful in understanding the epidemiology of the disease and devising appropriate control interventions in this region. Methodology. A hospital-based cross-sectional study involving pregnant women was conducted at two antenatal clinics in Mwanza between May and July 2019. The pretested structured questionnaire was used for data collection. Blood samples were collected aseptically from all consenting women followed by the detection of B. melitensis antibodies using slide agglutination test. Descriptive data analysis was done using STATA version 17. Results. A total of 635 pregnant women were enrolled with the median age of 25 (interquartile range (IQR): 16-48) years and median gestation age of 21 (IQR: 3-39) weeks. Seropositivity of B. melitensis antibodies was 103 (16.2 (95% CI:13.3-19.1)). On the multivariate logistic regression analysis, as the gestation age increases, the odds of being seropositive decreases (aOR:0.972 (95% CI: 0.945-0.999), P=0.045). Furthermore, being a housewife (aOR:3.902 (95% CI:1.589-9.577), P=0.003), being employed (aOR:3.405 (95% CI:1.412-8.208), P=0.006), and having history of miscarriage (aOR:1.940 (95% CI:1.043-3.606), P=0.036) independently predicted B. melitensis seropositivity among pregnant women in Mwanza. Conclusion. High seropositivity of B. melitensis was observed among employed and housewife pregnant women in Mwanza. This calls for the need of more studies in endemic areas that might lead to evidence-based control interventions.